Risk Factors for Cardiovascular Disease - Chahine, Johnny (IntechOpen, 2022)
Risk Factors for Cardiovascular Disease raises awareness about the importance of early recognition and prevention of modifiable cardiovascular risk factors. Some non-modifiable factors, like diabetes, can even be impacted by lifestyle modification (like weight loss) early in the disease. This book also describes cardiovascular risk factors in different patient populations and work settings.